Weak environmental controls on the composition and diversity of medium and large‐sized vertebrate assemblages in neotropical rain forests of the Guiana Shield. Issue 11 (22nd June 2018) - Denis, Thomas; Hérault, Bruno; Brunaux, Olivier; Guitet, Stéphane; Richard‐Hansen, Cécile
Abstract: Aim: Despite their often high‐trophic position and their contribution to many ecosystem functions, little is known about the factors affecting assemblage structure of medium‐ and large‐sized neotropical vertebrates. We examined the relative roles played by the physical and biological environment, and by purely spatial processes, in shaping the composition and diversities of these vertebrate assemblages. Then, based on the theory that the Guianan forest cover shrank to isolated pockets during the late Pleistocene–Holocene, we tested if the past forest refugia may have shaped current vertebrate assemblages. Location: French Guiana, Guiana Shield, South America. Methods: Abundances of 19 medium‐ and large‐sized vertebrates were estimated at 21 locations in undisturbed Guianan rain forests. Using taxonomic, functional and phylogenetic metrics, we partitioned the effects of a range of physical and biological environmental conditions and purely spatial predictors in shaping both assemblage composition and (alpha and beta) diversities. Results: We identified a significant, but weak relationship between taxonomic, functional and phylogenetic assemblage composition and environmental conditions. Assemblage diversity patterns were mainly explained by spatial predictors irrespective of the metrics. Current assemblage diversities are correlated with Pleistocene–Holocene forest history, with the highest alpha diversities outside of putative forest refugia, and the highest beta diversities inside these areas. Main conclusions: Current vertebrate assemblage composition is not strongly marked by common environmental factors. Our main conclusion is that assemblage composition results from individual species responses to the environment. Our findings also suggest that dispersal‐related processes or more probably historical processes shape (alpha and beta) diversity patterns. In fact, forest fragmentation during Pleistocene–Holocene climate changes could have led to isolated vertebrate assemblages evolving into unique species assemblages creating the current high beta diversity inside refugia, whereas the lower habitat stability outside of refugia could have led to mixed assemblages in areas recolonized by forest vertebrates (current high alpha diversity outside of refugia).